2020
DOI: 10.1021/acs.bioconjchem.0c00191
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Nucleoside Probe for the Inhibition of the Human Immunodeficiency Virus-Type 1 Reverse Transcriptase

Abstract: Nucleoside analogs have proven effective for the inhibition of viral polymerases and are the foundation of many antiviral therapies. In this work, the antiretroviral potential of 6-azauracil analogs was assessed using activity-based protein profiling techniques and functional assays. Probes based on the 6-azauracil scaffold were examined and found to bind to HCV polymerase and HIV-1 reverse transcriptase through covalent modification of residues near the active site. The modified sites on the HIV-1 RT were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…To further highlight the prospective application of this protocol in the synthesis of bioactive molecules, we attempted to prepare some pivotal pharmaceutical intermediates. As illustrated in Scheme , when 4-(prop-2-yn-1-yl)-1,2,4-triazine-3,5­(2 H , 4 H )-dione ( 1ar ) was chosen as a special substrate, the corresponding product 3ar was isolated in 54% yield, which could be readily transformed into Azauracil-AzT as an HIV-1 RT inhibitor through a click reaction …”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…To further highlight the prospective application of this protocol in the synthesis of bioactive molecules, we attempted to prepare some pivotal pharmaceutical intermediates. As illustrated in Scheme , when 4-(prop-2-yn-1-yl)-1,2,4-triazine-3,5­(2 H , 4 H )-dione ( 1ar ) was chosen as a special substrate, the corresponding product 3ar was isolated in 54% yield, which could be readily transformed into Azauracil-AzT as an HIV-1 RT inhibitor through a click reaction …”
Section: Resultsmentioning
confidence: 67%
“…So, the combination of 1,2,4-triazine-3,5­(2 H , 4 H )-dione and tetrahydrofuran into candidate drug molecules is a great promising strategy to develop new medicines. In 2020, the Pezacki group demonstrated that the bifunctional inhibitor Azauracil-AzT was highly effective in inhibiting HIV-1 reverse transcriptase activity . However, the study on the medicinal properties of the 1,2,4-triazine-3,5­(2 H , 4 H )-dione and tetrahydrofuran conjugated compounds is restricted because of the scarcity of their concise and convenient preparation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the first‐line drug Efavirenz, the bifunctional inhibitor suppressed Gag expression in HIV‐1 permissive T cells without cytotoxicity. Compound 48 (Figure 36), which covalently binds a chain‐terminating nucleoside derivative at the active site of reverse transcriptase, preventing its removal and lowering enzymatic activity, was therefore found to be a viable option for lowering HIV‐1 [98] …”
Section: Role Of Nitrogen‐containing Heterocyclic Compounds In Inhibi...mentioning
confidence: 99%
“…Compound 48 (Figure 36), which covalently binds a chain-terminating nucleoside derivative at the active site of reverse transcriptase, preventing its removal and lowering enzymatic activity, was therefore found to be a viable option for lowering HIV-1. [98] To explore positional flexibility with HIV-1 RT, Jin and his team, synthesized a group of new diary triazines (DATAs). Among all synthesized compounds reported to be most having EC 50 = 340.9 nmol/L and EC 50 = 307 nmol/L respectively which is comparable to the standard drug, ETR in MT-4 cells.…”
Section: Miscellaneous Nitrogen-containing Rt Inhibitorsmentioning
confidence: 99%
“…Recently, novel HIV‐1 reverse transcriptase inhibitors using zidovudine ( 1 ) have been investigated [16] . A nucleoside analogue of the azide grouped zidovudine ( 1 ) complexed with the ethynyl‐grouped azauracil by Huisgen cycloaddition displayed HIV‐1 reverse transcriptase inhibitory activity (Scheme 4).…”
Section: Nrtis That Target Hiv‐1mentioning
confidence: 99%